Input multiplicity analysis in a non-isothermal CSTR for acid-catalyzed hydrolysis of acetic anhydride - Jayakumar, Natesan Subramanian; Hashim, Mohd Ali; Thomas, M.T. (Wiley, 2010)
Multiplicity analysis gives practical guidance for process design to eliminate difficult operating regions associated with input and output multiplicities. Continuous stirred tank reactors (CSTRs) present challenging operational problems due to complex behavior such as input and output multiplicities, ignition/extinction, parametric sensitivity, and nonlinear oscillations. In the absence of a unified mathematical theory for representing various nonlinear system characteristics, the present study was aimed at understanding the dynamic behavior of CSTRs by means of experiments and to link the experimental data to theoretical considerations for further detection and elimination of operating problems. Theoretical modeling and analysis of a non-isothermal CSTR with acid-catalyzed hydrolysis of an acetic anhydride system for input multiplicity are discussed. Theoretical modeling of a non-isothermal CSTR using a root-finding technique was carried out for predicting steady-state temperatures. Alternatively, a mathematical model for a non-isothermal CSTR using unsteady-state mass and energy balance equations is proposed. Computer-based simulation was carried out using a program developed in MATLAB for final transient temperature and time-temperature data of the CSTR system under investigation. The results of a theoretical analysis conducted for confirming the existence of input multiplicity in non-isothermal CSTRs with acid-catalyzed hydrolysis of acetic anhydride were compared with experimental investigations for validation.